Impact of Behavioral Risk Factors on Mortality Risk in Older Korean Women - Shinuk Kim; Hyunsik Kang (Tehran University of Medical Sciences, 2022)
Background: To investigate the impact of lifestyle risk factors on all-cause and cardiovascular disease (CVD) mortality in Korean women aged 60 yr and older. Methods: Data (n = 3,034) obtained from the Korean longitudinal study of aging were analyzed. Exposures included lifestyle risk factors, such as smoking, alcohol abuse, underweight/obesity, physical inactivity, and unintentional weight loss. Primary outcomes were premature deaths from specific and all-causes. Results: During 9.6±2.0 yr of follow-up, there were 628 cases (20.7%) of death from all causes, of which 137 cases (4.5%) were from CVD. Compared to zero risk factor (hazard ratio, HR=1), crude HR of all-cause mortality was 2.277 (95% confidence interval, CI, 1.712 ~ 3.030, P < 0.001) for one risk factor, 2.977 (95% CI, 2.124 ~ 4.003, P < 0.001) for two risk factors, and 5.154 (95% CI, 3.515 ~ 7.557, P < 0.001) for three or more risk factors. Compared to zero risk factor (HR=1), crude HR of CVD mortality was 2.035 (95% CI, 1.422 ~ 2.913, P < 0.001) for one risk factor, 2.468 (95% CI, 1.708 ~ 3.567, P < 0.001) for two risk factor, and 4.484 (95% CI, 2.830 ~ 7.102, P < 0.001) for three or more risk factors. Adjusted HRs of all-cause (P = 0.016) and CVD (P = 0.050) for three or more risk factors only remained significant for three or more risk factors. Conclusion: The current findings showed that individual and combined lifestyle risk factors were significantly associated with increased risks of all-cause and CVD mortality in older Korean women.